2018
DOI: 10.1017/s1049023x18000316
|View full text |Cite
|
Sign up to set email alerts
|

Needle Thoracostomy: Does Changing Needle Length and Location Change Patient Outcome?

Abstract: Changing the timing, length of needle, and location of placement did not change mortality in patients requiring NT. Needle thoracostomy was used more frequently after the change in policy, and the MAL cohort was less injured. No increase in reported complications was noted. WeichenthalLA, OwenS, StrohG, RamosJ. Needle thoracostomy: does changing needle length and location change patient outcome? Prehosp Disaster Med. 2018;33(3):237-244.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…20 Three studies found a statistically significant mortality decrease when NCD was reported successful by the prehospital clinician. 19,28,29 The mortality was not associated with the needle length. 19,28 Using FT, the decompression success rate ranged between 9.7% to 32.0%.…”
Section: Efficacy Clinical Outcomes and Adverse Eventsmentioning
confidence: 91%
See 4 more Smart Citations
“…20 Three studies found a statistically significant mortality decrease when NCD was reported successful by the prehospital clinician. 19,28,29 The mortality was not associated with the needle length. 19,28 Using FT, the decompression success rate ranged between 9.7% to 32.0%.…”
Section: Efficacy Clinical Outcomes and Adverse Eventsmentioning
confidence: 91%
“…A total of 1,420 unique citations were obtained by the literature search strategy, of which 20 original studies (two prospective cohort or case series and 18 retrospective cohort or cases series) fulfilled the inclusion criteria. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Each study included between 24 and 2,574 patients and most studies (n = 9) were conducted in the United States of America. The main mechanism was blunt trauma.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations